(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In 2011, 4397 suspect rabid animals were submitted for testing to the Canadian Food Inspection Agency diagnostic laboratories in Ottawa, Ontario and Lethbridge, Alberta. Of these, 115 (2.6%) tested positive in the fluorescent antibody test (FAT). Additionally, enhanced wildlife surveillance samples from Ontario (ON, n=185) and Alberta (AB, n=88) were tested and found to be negative. The majority of rabies cases were detected in the province of Saskatchewan (n=34), followed by ON (n=26), Manitoba (n=21), Quebec (n=17), British Columbia (n=7), Northwest Territories (n=6) and Nunavut (n=4). No cases were found in AB, Yukon Territories, or the Atlantic provinces, although with the exception of AB, samples submissions were very low (1 to 40 samples) from these regions. The striped skunk (Mephitis mephitis) was the species most frequently found positive (n=42), followed by big brown bat (Eptesicus fuscus, n=35), Arctic fox (Vulpes lagopus, n=11) and red fox (V. vulpes, n=5). Spillover of wildlife rabies variants into domestic animals was observed in 1 bovine and 1 dog (Arctic fox variant), and in 4 cats, 2 horses and 1 dog (Western skunk variant). The remaining positive cases were found in various bat species. Positive cases involving human exposures originated from 33 different counties, whereas those with only domestic animal exposures or no exposures noted came from 58 and 14 counties, respectively. Of the 105 counties represented only 6 were common to two or more exposure categories. While 1% of samples with human exposures tested positive, 10.6% of those with domestic animal exposure, and 5.2% of those with no exposure indicated tested positive for rabies. In addition to the animal samples, seven human suspect cases were tested by RT-PCR and/or FAT on saliva and nuchal skin biopsy samples; all were negative for rabies.